Pre and Post Earthquake Slope Stability Analysis Using Equivalent Linear Method – a Case Study of Jure Landslide - Shrestha, R.; Tiwari, R.C. (Journal of Advanced College of Engineering and Management, 2023)
Slope stability analysis is one of the most important tools to determine the stability of both natural as well as man-made slopes. The main objective of this study is to compare safety factor of the Jure landslide before and after an earthquake occurrence using Geostudio QUAKE/W module. Three different positions of water table (top, middle and bottom of debris) were considered for the study. The safety factors of both deterministic and probabilistic case are determined. The Gorkha Earthquake's time history data were taken into consideration. Both the bedrock and debris are modeled using the equivalent linear approach for dynamic analysis. The findings indicate that the slope was on the verge of failing prior to the earthquake and is predicted to fail following the earthquake event that was taken into account.